EMPOWERING ISLAMIC BOARDING SCHOOL IN IMPROVING ITS HUMAN RESOURCES IN BATANG HARI REGENCY JAMBI PROVINCE (THE STUDY AT UMMUL MASAKIN ISLAMIC BOARDING SCHOOLS IN BATANG HARI REGENCY) - Maisah; Yamin, H. Martinis; Yamin, H. Martinis; Madyan (International Journal of Research -GRANTHAALAYAH, 2019)
The existence of Islamic boarding schools in Jambi province, present as a place which give image to Islamic boarding schools that familiarize students to recognize and to study religious knowledge in depth by applying it in the daily lives of the students. Therefore, it will become a habit in the students behavior. Ummul Masaqin Islamic Boarding School is one of the modern Islamic boarding schools which proclaims itself as an open-minded mass organization in the hope that it can be more flexible and more agile to play an active role in solving social problems. By continuous development of the times, the students are expected to be able to follow these developments. Islamic Boarding Schools see the importance of developing the function of Islamic boarding schools as a center for scientific and religious development, and as a center for the empowerment of students. Therefore, Islamic Boarding Schools made a new breakthrough by carrying out empowerment strategy for their students. This empowerment strategy is an effort of Islamic Boarding Schools to increase the resources of the students. This research is a field research that uses qualitative research method or approach. The focus of the research is centered on the issue of empowering Islamic boarding school in improving its human resources in Jambi Province, by using data collection techniques: observation, interviews and documentation. The type of data used is primary and secondary data. The data validity technique uses data triangulation. The research findings are: 1) Ummul Masakin Islamic Boarding School teaching and educating staff recruitment is conducted by planning through estimation of employee requirements and estimation of internal supply of human resources. 2) The empowerment of Islamic boarding schools in improving human resources in the Islamic Boarding School in Batang Hari conductedin the form of (a) Recitation, (b) Al-Qur’an Educational Park, (c) Poskenstren, (d) Kopontren. 3) Islamic Boarding Schools prepares future scholars by empowerment in Ummul Masakin Islamic Boarding School through various activities / coaching, namely: (a) The Development of the Khitabah, (b)The Development of the Kitab Kuning Study.